COVID-19 AND LITERATURE, FORMS OF SELF-ACTUALIZATION AND TEACHER DEVELOPMENT IN TOURISM, ARTS AND CULTURE - Maryelliwati Maryelliwati; Hari Adi Rahmad (ppjbsip, 2020)
The concept that underlies the learning of cultural arts is absolute for teachers which is based on meeting the needs of students in studying cultural arts in schools. The needs of these students, if it is related to the context of the development of the community's outlook on life, because after all students will eventually return to live and play a role in the social environment. The development of cultural arts for teachers is an important thing, especially during the corona period is a form of Higher Education Tri Dharma that must be done. The result is that the teacher is able to teach and understand and understand what the teacher needs as a capital to continue to exist, especially during the corona pandemic.AbstrakKonsep yang mendasari pembelajaran seni budaya adalah mutlak bagi guru yang didasarkan pada pemenuhan kebutuhan apa yang perlu bagi peserta didik dalam mempelajari seni budaya di sekolah. kebutuhan peserta didik ini, jika dikaitkan konteks perkembangan pandangan hidup masyarakat, karena bagaimana pun peserta didik pada akhirnya akan kembali hidup dan berperan dalam lingkungan bermasyarakat. Pengembangan seni budaya kepada guru merupakan suatu hal yang penting apalagi pada masa corona adalah salah bentuk Tri Dharma Perguruan Tinggi yang harus dilakukan. Hasilnya dalah guru mampu mengajarkan dan memahami serta mengerti seperti apa yang dibutuhkan guru sebagai modal untuk tetap eksis, apalagi pada masa pandemi corona.